2018
DOI: 10.1038/s41390-018-0090-0
|View full text |Cite
|
Sign up to set email alerts
|

The effects of sleeping position, maternal smoking and substance misuse on the ventilatory response to hypoxia in the newborn period

Abstract: The altered response to hypoxia in the prone position of infants whose mothers substance-misused and smoked in pregnancy may explain their increased vulnerability to SIDS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…These studies have shown that prone sleep position may alter the autonomic control of the infant cardiovascular system, particularly at 2 to 3 months of age, and may result in decreased cerebral oxygenation [3,4]. Prone position was also shown to decrease cardiac output, mean arterial pressure, oxygen saturation, minute ventilation, and arousal responses to various stimuli [5][6][7][8].…”
Section: Resultsmentioning
confidence: 99%
“…These studies have shown that prone sleep position may alter the autonomic control of the infant cardiovascular system, particularly at 2 to 3 months of age, and may result in decreased cerebral oxygenation [3,4]. Prone position was also shown to decrease cardiac output, mean arterial pressure, oxygen saturation, minute ventilation, and arousal responses to various stimuli [5][6][7][8].…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the nature of the respiratory stressor causing the SIDS, our experiments indicate that the combination of low O 2 with high CO 2 results more deleterious than hypoxia or hypercapnia separately since by themselves they did not induce sudden death; this is likely because the disturbances in the generation of ETBs worsen arterial O 2 saturation; thus, a defective generation of ETBs, like are those previously reported defects in sighs, arousals, and gasping (Garcia et al, 2013 ), would be considered as a physiological biomarker of susceptibility in SIDS. Abnormalities of breathing control may cause SIDS either by hyporesponsive chemoreflexes that may allow hypoxia to persist without an adequate response or by destabilizing hyperresponsive chemoreflexes (Cummings et al, 2011 ; Gauda et al, 2007 ; Rossor et al, 2018 ) as seem to be the case of the Cx36KO mice. In the stereotyped cascade of events leading to the respiratory arrest in the neonatal Cx36KO mice, we have identified two pathophysiological determinants not previously reported: the early collapse in the generation of EBTs, which accelerates heart rate and worsens the O 2 saturation, and the generation of a paroxysmal clonic‐tonic generalized motor discharge that provokes the definitive cessation of eupneic rhythm and the starting of gasping respiration, and precipitates the collapse of heart rate.…”
Section: Discussionmentioning
confidence: 99%
“…These differences remained significant when adjusting for differences in birthweight, age and sex (20,21). Furthermore, maternal smoking and substance abuse particularly impair the response to hypoxia in the prone position (22). This maladaptive response can be explained by the infant's chronic exposure to fetal hypoxia, leading to persistent, inappropriate activation of the respiratory neural network underlying the biphasic ventilatory response (21,23).…”
Section: Physiological Abnormalities In Infants Of Mothers Who Smokedmentioning
confidence: 99%